Peran Inovasi Dalam Memediasi Pengaruh Karakteristik Dan Orientasi Kewirausahaan Terhadap Kinerja - Farha Kamilatun Nuha Anwar; Meldona , Meldona; Yuliati, Yuliati; Adhitya Salman Alfarisyi; Zaeniko Saputra (CV. AFDIFAL MAJU BERKAH, 2023)
Micro, Small and Medium Enterprises (MSMEs) are strategically important in the Indonesian economic system. Entrepreneurs play an important role in managing business operations to achieve high performance. Performance is influenced by entrepreneurial characteristics and orientation mediated by innovation to achieve business success. This study aims to provide empirical evidence on the influence of entrepreneurial characteristics and orientation towards performance mediated by innovation at coffee shops in Malang City. This research is quantitative research using a questionnaire instrument conducted on a research sample of 145 members of the Malang Coffee Lovers Community. Data analysis was performed using PLS-SEM SmartPLS 3.2.9. The results showed that characteristics and entrepreneurial orientation have a significant positive effect on performance, and the innovation plays a role as mediator between characteristics and entrepreneurial orientation towards performance. The high performance in the coffee field could be achieved if MSME actors as entrepreneurs pay attention to their daily attitude characteristics, especially in terms of experience in quality coffee business management and its production, and also have an entrepreneurial orientation, especially by paying attention to the commitment to innovate so that they can produce coffee product innovations which then also have an impact on improving performance in the form of increasing optimal operating profits